ADP-ribosylation factor is functionally and physically associated with the Golgi complex. - Stearns, T (1990)
ADP-ribosylation factor (ARF) is a ubiquitous, highly conserved 21-kDa GTP-binding protein, first identified in animal cells as the cofactor required for the in vitro ADP-ribosylation of the stimulatory regulatory subunit of adenylate cyclase, Gs, by cholera toxin. As the relevance of this activity to in vivo function is unknown, we have taken advantage of the conserved nature of ARF to study its function in Saccharomyces cerevisiae. Yeast cells bearing an arf1 null mutation display a number of phenotypes suggesting a defect in the secretory pathway. Secreted invertase is only partially glycosylated, and there is a small internal accumulation of invertase. Genetic experiments revealed interactions between ARF1 and other genes known to be involved in the secretory pathway, including YPT1, which encodes a different GTP-binding protein. In accord with these genetic results, immunofluorescence and immunoelectron microscopy show that ARF protein is localized to the Golgi apparatus in mammalian cells, in particular to the cytosolic surface of predominantly cis-Golgi membranes. Together, these results indicate that ARF functions in intracellular protein transport to or within the Golgi apparatus, a role not predicted by the previous in vitro biochemical studies.